Assessing Reliability and Validity of the Persian version of Infertility Stigma Scale (ISS) in Infertile Women - Gholamreza Rajabi; Jila Amiri Asl; Arash Jelodari (Hamadan University of Medical Sciences, 2017)
Background: Stigma is accounted important structure in mental health areas, and one of the most important is infertility disorder consequences. The aim of the current research was to evaluate reliability and validity of the Persian version of Infertility Stigma Scale among infertile women. Methods: The current research was psychometric of methodological type. One hundred and sixty six infertile women were selected using purposive sampling method and via interviews from Jahad Daneshgahi Infertility Treatment Center of Khuzestan. They filled out the Infertility Stigma, Rosenberg Self-esteem, General self-efficacy Beliefs and Self-Criticism scales. Data were analyzed using confirmatory factor analysis and fitness indices and by Amos and SPSS-21 software. Results: In the exploratory factor analysis using Varimax rotation in the Persian of the Infertility Stigma Scale four factors extracted: Personal devaluation, social withdraw, general stigma, and family stigma that accounted for 62.49% of the variance. Also, Cronbach's α coefficients (internal consistency) were satisfactory for the whole scale and in extracted four factors, test-retest  reliability coefficient of the scale with two-week interval was 0.58 and its divergent validity coefficient with Rosenberg Self-esteem and General Self-efficacy Scales and its convergent validity with Self-criticism Scale were statistically significant (P < 0.001). Conclusions: Given the appropriate validity and reliability of the scale, it can be used for research activities among this type of population and in infertility research and therapeutic center.